2022
DOI: 10.3389/fimmu.2022.858383
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Elite: Lessons From HIV-1 Controllers and Animal Models on Trained Innate Immunity and Virus Suppression

Abstract: Although antiretroviral therapy (ART) has drastically changed the lives of people living with human immunodeficiency virus-1 (HIV-1), long-term treatment has been associated with a vast array of comorbidities. Therefore, a cure for HIV-1 remains the best option to globally eradicate HIV-1/acquired immunodeficiency syndrome (AIDS). However, development of strategies to achieve complete eradication of HIV-1 has been extremely challenging. Thus, the control of HIV-1 replication by the host immune system, namely f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 151 publications
1
7
0
Order By: Relevance
“…On the contrary, higher expression NKp46 activating receptor has been reported in circulating NK cells from EC [21]. Finally, interaction between protective HLA-B∗57 and KIR3DL1 and KIR3DS1 in EC can suppress viral replication [21,41 ▪ ]. HLA-B∗57 has also been reported to play a role in viral control by CD8 + T cells, and although no evidence of synergy has yet been found, it highlights the importance of NK cells responses on EC to maintain viral control.…”
Section: Innate Immune Response In Natural Hiv-1 Controllersmentioning
confidence: 96%
See 4 more Smart Citations
“…On the contrary, higher expression NKp46 activating receptor has been reported in circulating NK cells from EC [21]. Finally, interaction between protective HLA-B∗57 and KIR3DL1 and KIR3DS1 in EC can suppress viral replication [21,41 ▪ ]. HLA-B∗57 has also been reported to play a role in viral control by CD8 + T cells, and although no evidence of synergy has yet been found, it highlights the importance of NK cells responses on EC to maintain viral control.…”
Section: Innate Immune Response In Natural Hiv-1 Controllersmentioning
confidence: 96%
“…Interestingly, circulating cDC from EC display higher capacities of antigen presentation associated with higher expression of activating immunomodulatory receptors such as Leukocyte Immunoglobulin-Like Receptor subfamily B (LILRB1) and LILRB3 [20]. Previous studies reported that improved detection of HIV-1 transcripts by the Cyclic GMP-AMP Synthase pathway in cDC which might contribute to activation of CD8 þ T cells in HIV-1 controllers [5,21]. Subsequent transcriptional studies at the single-cell level identified an activation state of circulating cDC from EC characterized by high interferon gene expression signatures regulated by TANK-Binding Kinase 1, co-expression of high levels of CD64 and Programmed Death-Ligand 1 (PD-L1) and superior functional capacities to activate polyfunctional HIV-1-specific CD8þ T cell responses [6].…”
Section: Role Of Dendritic Cellsmentioning
confidence: 99%
See 3 more Smart Citations